Value of temporal muscle thickness in predicting outcomes of stroke: a systematic review and meta-analysis - Fang, Min; Wang, Fangjun; Sheng, Yu; Qiu, Shengchen (Frontiers in Neurology, 2025)
ObjectiveThis systematic review examined if temporal muscle thickness (TMT) as a surrogate marker of sarcopenia was a predictor of outcomes after stroke.MethodsWe explored the PubMed, Embase, Scopus, and Web of Science databases till 18th January 2025 for studies reporting stroke prognosis based on baseline TMT. Pooled analyses examined associations with post-stroke mortality, functional outcomes, and dysphagia. Meta-regression was conducted using baseline NIHSS and TMT values as moderators.ResultsNine studies were available. Meta-analysis showed that low TMT was associated with a statistically significant increase in the risk of post-stroke mortality (OR: 1.42 95% CI: 1.03, 1.96 I2 = 43%). A pooled analysis of five studies showed that there was a tendency for good functional outcomes with high TMT (OR: 1.24 95% CI: 1.00, 1.54 I2 = 75%). But the results were non-significant. Two studies showed that baseline TMT was significantly associated with an increased risk of dysphagia. Meta-regression did not identify significant moderating effects.ConclusionPreliminary evidence suggests that lower TMT is associated with higher mortality after stroke, while associations with functional recovery remain inconclusive. Current limitations, including heterogeneity and lack of sex-specific analyses, preclude routine clinical use. Further standardized and patient-level research is warranted.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025637925.